Effect of Leukocyte-Platelet-Rich Fibrin on Bone Loss Following Dental Extraction. - Zeeshan Ahsan; Ammar Ali Khalid; Abdul Rehman; Bisma Mir; Wasif Askari (International Journal of Endorsing Health Science Research, 2023)
Dental extraction often leads to bone loss, posing challenges for oral rehabilitation. This narrative review aimed to evaluate the effect of leukocyte-rich platelet-rich fibrin (L-PRF) on bone loss following dental extraction in healthy patients. A systematic search of the PubMed database was conducted, resulting in the inclusion of six randomized controlled studies. The review found evidence suggestive of less bone loss and improved healing after extraction when L-PRF was utilized. L-PRF, derived from the patient's blood, offers a promising approach with its growth potential and ability to provide a scaffold and matrix for wound healing and bone regeneration. While numerous studies have demonstrated the benefits of L-PRF in alveolar ridge preservation, more randomized controlled studies with larger sample sizes are warranted to fully understand its application in different clinical conditions and enhance oral health outcomes.